Virulance factors of Enterococcus faecalis: a literature review - Romero Romero , Diego Patricio (2025)
Enterococcus faecalis (E. faecalis) is a Gram-positive coccus, its genus represents a significant health risk to humans due to its high proliferative capacity, survival in hostile environments and production of various virulence proteins (hemolysins, bacteriocins, proteases, agglutinins); combined with its resistance to antimicrobials, this pathogen poses a serious concern to healthcare systems. The aim of this bibliographic research was to highlight the virulence factors (VF) of E. faecalis, whose dissemination will facilitate insight into the molecular mechanisms underlying the conditions caused by this bacterium. It was found that, at the oral level, E. faecalis is characterized by the formation of resistant biofilms with high adaptability and proliferation rates, leading to considerable infectious episodes that are resistant to treatment with certain antibiotics. Therefore, to control these episodes, appropriate antibiotic therapy, in addition to mechanical treatment, is necessary. It is concluded that the VF of E. faecalis determine the clinical complexity of the infectious conditions caused by its proliferation, and antibiotic sensitivity testing are often required to determine the most effective pharmacological treatment.